MIDDLE EAST REGION - Ahmedova Muhayyo; Maxkamova Diyora; Abdulhakimova Mohlaroyim Baxodirjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The Middle East tourist region in Southeast Asia located in the Arab countries and in the north of Africa Includes the Arab Republic of Egypt and Libya. This is touristic the region includes a total of 14 countries. The region is geographical, a large area that is historically and socio-economically diverse occupies.